Developing Dayak Culture-Based Digital Comic Media for Enhancing Geometry Literacy Among Fifth-Grade Elementary Students - Angellina, Angellina; Kusuma, Dani (Journal of Innovation and Research in Primary Education, 2025)
Mathematics education in Indonesian elementary schools faces significant challenges in improving students' understanding of abstract geometric concepts. Traditional teaching methods often fail to engage students and connect mathematical concepts to real-world contexts, resulting in low mathematics literacy scores. This study employed a Research and Development (R&D) approach using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) to develop a digital comic learning media integrating Dayak cultural elements for teaching geometry to fifth-grade elementary students. The study involved 10 students and utilized both qualitative and quantitative data collection methods, including pre-post tests, questionnaires, interviews, and observations. The developed digital comic media demonstrated high validity with media expert validation scoring 100% and material validation scoring 50%. Student practicality assessment achieved 75%, while teacher practicality assessment reached 78%. The effectiveness evaluation showed moderate improvement with an N-gain score of 0.55, indicating enhanced student understanding of geometric concepts. However, statistical analysis revealed no significant difference between pretest and posttest scores (p > 0.05), though mean scores increased from 68 to 75. The digital comic learning media successfully integrated Dayak cultural elements with geometry education, creating contextual and engaging learning experiences. The media proved practical and feasible for classroom implementation, effectively connecting abstract mathematical concepts to familiar cultural objects. While statistical significance was not achieved, the moderate improvement in student understanding suggests potential for enhancing mathematics literacy through culturally-responsive digital learning materials.